ANALISIS PENGARUH KUALITAS INFORMASI, KEMUDAHAN PENGGUNAAN DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN GENERASI Z PADA E-COMMERCE SHOPEE - Cornelius Tristan Radja Noviandra, (2023)
The rapid development of the internet has made the development of e-commerce or online trading a new event in the Indonesian economy. Electronic Commerce and E-commerce are buying and selling activities through online media that utilize the internet, which does not need to meet face to face between sellers and buyers but uses online media as intermediaries. This research was conducted using a quantitative method with the aim of proving and analyzing the influence between the quality of information, convenience and lifestyle and purchasing decisions on e-commerce shopee. The population in this study is generation Z in Jakarta Province who have made transactions at Shopee. The sample size is 100 respondents obtained through the non-probability method with purposive sampling. This study uses primary data obtained through distributing questionnaires and analyzed using the Partial Least Square (PLS) analysis method through the Smartpls 4 application. The results in this study indicate that there is an influence between information quality, ease of use and lifestyle on purchasing decisions.